Patellar Tendon Shear Wave Velocity Is Higher and has Different Regional Patterns in Elite Competitive Alpine Skiers than in Healthy Controls - Götschi, Tobias; Hanimann, Jonas; Schulz, Nicole; Huser, Simon; Held, Victoria; Frey, Walter O.; Snedeker, Jess G.; Spörri, Jörg (Frontiers in Bioengineering and Biotechnology, 2022)
Competitive alpine skiers are exposed to enormous forces acting on their bodies – particularly on the knee joint and hence the patellar tendon - during both the off-season preparation and in-season competition phases. However, factors influencing patellar tendon adaptation and regional pattern differences between alpine skiers and healthy controls are not yet fully understood, but are essential for deriving effective screening approaches and preventative countermeasures. Thirty elite competitive alpine skiers, all members of the Swiss Alpine Ski Team, and 38 healthy age-matched controls were recruited. A set of two-dimensional shear wave elastography measurements of the PT was acquired and projected into three-dimensional space yielding a volumetric representation of the shear wave velocity profile of the patellar tendon. Multivariate linear models served to quantify differences between the two cohorts and effects of other confounding variables with respect to regional shear wave velocity. A significant (p < 0.001) intergroup difference was found between skiers (mean ± SD = 10.4 ± 1.32 m/s) and controls (mean ± SD = 8.9 ± 1.59 m/s). A significant sex difference was found within skiers (p = 0.024), but no such difference was found in the control group (p = 0.842). Regional SWV pattern alterations between skiers and controls were found for the distal region when compared to the mid-portion (p = 0.023). Competitive alpine skiers exhibit higher SWV in all PT regions than healthy controls, potentially caused by long-term adaptations to heavy tendon loading. The presence of sex-specific differences in PT SWV in skiers but not in controls indicates that sex effects have load-dependent dimensions. Alterations in regional SWV patterns between skiers and controls suggest that patellar tendon adaptation is region specific. In addition to the implementation of 3D SWE, deeper insights into long-term tendon adaptation and normative values for the purpose of preventative screening are provided.